2019
DOI: 10.30682/nm1904a
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Innovative Technologies Adoption by Livestock Holders in Arid Area of Tunisia

Abstract: Despite the efforts to enhance adoption of innovative technologies (IT) by the Tunisian Government through national and/or international development projects, the potential rate of adoption of these technologies has remained low among farmers. This study aims at shedding some light on the potential factors that influence IT adoption in the Tunisian arid areas. Technological, economic, institutional factors and human specific factors (social) are selected to be the determinants of agricultural technology adopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
55
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 16 publications
11
55
1
4
Order By: Relevance
“…Similar results were reported by Boz et al (2011) and Boz (2014). However, these results are not congruent with those of Aksoy et al (2011) and Dhraief et al (2018), which concluded that there was a negative correlation between the farmers' age and the adoption of innovations. Thus, it can be said that it is important to make informative meetings about the innovations that can be applied in dairy farming activity to young and middle-aged farmers in the research area and striving towards increase their tendency to adopt innovations.…”
Section: Resultscontrasting
confidence: 81%
“…Similar results were reported by Boz et al (2011) and Boz (2014). However, these results are not congruent with those of Aksoy et al (2011) and Dhraief et al (2018), which concluded that there was a negative correlation between the farmers' age and the adoption of innovations. Thus, it can be said that it is important to make informative meetings about the innovations that can be applied in dairy farming activity to young and middle-aged farmers in the research area and striving towards increase their tendency to adopt innovations.…”
Section: Resultscontrasting
confidence: 81%
“…The household head with primary, secondary and university levels of education presented on average 2.26 ± 0.86, 1.85 ± 0.89 and 1.66 ± 0.61 AIs per conception. The present study results are consistent with the report by Bayei and Nache (2014) and Dhraief et al (2018) who suggest that the adoptions of new technologies are associated with education of the household head. Indeed, Ajala (2007) in Means in the same row with different superscripts differ (p < 0.05).…”
Section: Extrinsic Factors Influencing the Number Of Inseminations Pesupporting
confidence: 93%
“…The lowest number of IC (1.59 ± 0.67) was observed in the farms managed by a group of 35 to 49 years old farmers while the highest number of IC (2.00 ± 0.90 and 2.04 ± 0.87) was observed in the farms managed by young and older farmers (Below 35 and above 50 years, respectively). This difference within age groups could be justified by the fact that age of the household head has a negative effect on the adoption of new technologies including AI (Dhraief et al, 2018;Bayei and Nache, 2014;Zanu et al, 2012) and innovations (Howley et al, 2012). The old farmers tend to stick to what they used to and hardly venture into new ways of doing things including AI (Bayei and Nache, 2014).…”
Section: Extrinsic Factors Influencing the Number Of Inseminations Pementioning
confidence: 99%
“…Salt farmer participation in the extension had a positive and significant effect with p-value < 0.01 and marginal effect value of 0.2697, which means that the average probability of salt farmer to attend extension to decide on geoisolator implementation was 26.97 percent higher than that of farmers who did not attend the extension. This result is similar to study conducted by Beshir et al (2012) and Asmelash (2014) in Ethiopia, Dhraief et al (2018) in Tunisia, Kumar et al (2018) in aquaculture and Obiero et al (2019) in Kenya, Ahmed & Anang (2019) in Ghana that extension agents showed a significant effect on adoption level since the availability of information provided by extension agents is expected to stimulate adoption. The extension agent as a source of information related to geoisolator technology that has a strong influence on farmers' adoption decisions.…”
Section: Factors Affecting the Decision Of Salt Farmer To Adopt Geoissupporting
confidence: 91%